Urbanization Drives a Reduction in Functional Diversity in a Guild of Nectar-feeding Birds - Anton Pauw; Kirsten Louw (Ecology and Society, 2012)
Urbanization is a widespread and rapidly growing threat to biodiversity, therefore we need a predictive understanding of its effects on species and ecosystem processes. In this paper we study the impact of urbanization on a guild of nectar-feeding birds in a biodiversity hotspot at the Cape of Africa. The guild of four bird species provides important ecosystem services by pollinating 320 plant species in the Cape Floral Region. Functional diversity within the guild is related to differences in bill length. The long-billed Malachite Sunbird (Nectarinia famosa) plays an irreplaceable role as the exclusive pollinator of plant species with long nectar tubes. We analyzed the composition of the guild in suburban gardens of Cape Town along a gradient of increasing distance from the nearest natural habitat. Urbanization reduces the functional diversity of the nectarivore guild. Malachite Sunbirds did not penetrate more than 1 km into the city, whereas only the short-billed Southern Double-collared Sunbirds (Cinnyris chalybea) occurred throughout the urbanization gradient. The lack of data precludes conclusions regarding the detailed responses of Orange-breasted Sunbirds (Anthobaphes violacea) and Sugarbirds (Promerops cafer), however their absence across the entire gradient is suggestive of high sensitivity. The functional diversity of this guild of pollinators can potentially be restored, but the pros and cons of this conservation action need to be considered.